Perceptions of students about plagiarism: qualitative data (Encuentros, 2016)
The results of an investigation which revolved around the theme of university plagiarism are presented; this research aimed to identify the social representations (concepts and criteria) that members of the academic community about the plagiarism, in order to offer some strategies for prevention and weakening of the practice. To obtain data two instruments were used: a closed questionnaire and a semi-structured open-ended questionnaire. This article shows the perceptions of students from the Faculty of Humanities at National University around this problem based on the information from the open questionnaire. The data show that personal, social and academic factors explain behaviors of plagiarism. Among the former are the lack of time and vocational disorientation; and social factors, the precarious conditions in which teachers and low cultural capital of students work and academic factors as lack of support from teachers in academic writing processes and methodologies that do not promote the construction of knowledge. Reflect on these factors may decrease and combat plagiarism at universities.